The union role in economic globalization of Colombia (2013)
The economic, political, social and cultural changes as a result of the globalization process well mean a change in the nature of relations between states with the other actors of the international system were also meant a change in the structure and organization of the unions as political actors and social representatives of collective interests. New business models have limited their action to break big in small businesses, bringing diversification in the interests of workers as a response to the fragmentation of the production structure and outsourcing.